If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+18/6=x/3
We move all terms to the left:
5x+18/6-(x/3)=0
We add all the numbers together, and all the variables
5x-(+x/3)+18/6=0
We add all the numbers together, and all the variables
5x-(+x/3)+3=0
We get rid of parentheses
5x-x/3+3=0
We multiply all the terms by the denominator
5x*3-x+3*3=0
We add all the numbers together, and all the variables
-1x+5x*3+9=0
Wy multiply elements
-1x+15x+9=0
We add all the numbers together, and all the variables
14x+9=0
We move all terms containing x to the left, all other terms to the right
14x=-9
x=-9/14
x=-9/14
| 6n^2+2n=0 | | N=-p^2-6p+512400 | | (2/3+5x)=(5/6-6x) | | N=-p^2-6p+512 | | H=-16t^2+260 | | y/7=19 | | 2=1/2(7x+2) | | 2=1/2(7x+12) | | 5(x-4)+2=3x | | 0=10+2/5x | | 7x+3-22x+5=x+9 | | -27+2d=-6(3d+5) | | 16t^2-135t-81=0 | | 1/2n+7-2n-14=5n+1 | | (z=1.2)/5=3.6 | | x3+3x2+15=0 | | 10y+3-7y-9=0 | | 15-46=3(x-1)-7 | | 9x+13+12x-29=180 | | (5x-23)+(7x-1)=180 | | 6x+20=8x-10 | | 30x-60=300 | | 3.6*x=1.3(x+6) | | d=0.3×2.40 | | 3.6*x=1.3(x+4) | | x=0.35x+1 | | ∣2x−8∣=∣x+5∣∣2x−8∣=∣x+5∣ | | 3.6*x=1.2(x+4) | | 2(x+1)=x*1 | | 3.6*x=1.6(x+4) | | .5(5y-2)+.25(2y+5)=0 | | -3(t+-2)=8 |